2015
DOI: 10.1055/s-0035-1563539
|View full text |Cite
|
Sign up to set email alerts
|

Is a Profiled Annuloplasty Ring Suitable for Repair of Degenerative Mitral Regurgitation? A Single-Center Experience Comprising 200 Patients

Abstract: Background Various devices have been proposed for ring annuloplasty in patients with degenerative mitral valve disease. This study reports for the first time midterm results with the rigid three-dimensional Medtronic Profile 3D (Medtronic, Minneapolis, Minnesota, United States) annuloplasty ring. Methods Between June 2009 and June 2011, 200 patients (mean age 61 ± 13 years, 70% male) with severe degenerative mitral regurgitation underwent mitral valve repair using the Medtronic Profile 3D annuloplasty ring. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Among the mitral studies, 6 used semi-rigid [ 6 , 7 , 9 , 13 , 20 , 27 ], 5 used rigid [ 10 , 13 , 14 , 18 , 24 ], 5 used flexible [ 8 , 11 , 12 , 19 , 27 ] and 2 used biological rings [ 17 , 25 ]. The incidence of dehiscence among ring types was the following: 0.04% flexible; 1.55% semi-rigid; 2.96% rigid and 3.07% in biological (number of patients, respectively: 784; 3750; 608; 163).…”
Section: Resultsmentioning
confidence: 99%
“…Among the mitral studies, 6 used semi-rigid [ 6 , 7 , 9 , 13 , 20 , 27 ], 5 used rigid [ 10 , 13 , 14 , 18 , 24 ], 5 used flexible [ 8 , 11 , 12 , 19 , 27 ] and 2 used biological rings [ 17 , 25 ]. The incidence of dehiscence among ring types was the following: 0.04% flexible; 1.55% semi-rigid; 2.96% rigid and 3.07% in biological (number of patients, respectively: 784; 3750; 608; 163).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we observed a low reoperation rate due to recurrent MR in patients undergoing MV repair for functional MR. At latest follow-up, no patient presented with more than moderate mitral regurgitation. In previous studies from our institution, we have demonstrated that MV repair for functional MR was associated with low or no recurrent MR [ 10 , 11 , 12 ]. These findings resonate with prior evidence suggesting that high rates of recurrent MR may attenuate the potential benefits of mitral valve repair [ 2 , 3 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%